Nutritional Value and Bioactive Compounds Characterization of Plant Parts From Cynara cardunculus L. (Asteraceae) Cultivated in Central Greece - Petropoulos, Spyridon A.; Pereira, Carla; Tzortzakis, Nikolaos; Barros, Lillian; Ferreira, Isabel C. F. R. (Frontiers in Plant Science, 2018)
Cardoon (Cynara cardunculus L. var. altilis DC) is a perennial species of the Mediterranean basin and a multipurpose crop since the different plant parts have found various uses, including its use for human consumption or fodder and industrial uses. In the present study, the nutritional value of the edible parts (immature capitula) of cardoon plants was evaluated, while further analyses were carried out in order to assess antioxidant properties and phenolic compounds composition of the various plant parts and seed oils. Cardoon capitula (heads) were a rich source of carbohydrates, with the main detected free sugar being sucrose, as well as of macro- and microminerals (K, Ca, Mg and Fe). Heads were also abundant in saturated fatty acids (palmitic, behenic, linoleic, stearic, caproic and oleic acid), whereas seed oils in unsaturated fatty acids (linoleic, oleic, palmitic and stearic acid). Total phenolic compounds (TPC) content and phenolics composition differed between the various plant parts, with heads and leaf blades having higher TPC than midribs and petioles. Moreover, heads and leaf midribs and petioles consisted mainly of phenolic acids (5-O-caffeoylquinic and 3,5-O-dicaffeoylquinic acid), with flavonoids being detected in lower amounts. In contrast, the composition of polyphenols in leaf blades consisted mostly of flavonoids (Luteolin-7-O-glucoside and luteolin-7-O-malonylhexoside), whereas phenolic acids were also detected in considerable amounts (5-O-feruloylquinic and 3-O-caffeoylquinic acid). Regarding antioxidant properties, leaf blades and seeds exhibited the highest potency for all the tested assays which could be partly attributed to the synergistic effects of the phenolic compounds present in each sample. In conclusion, cardoon plant parts may find various uses in the food and pharmaceutical industry, since they contain considerable amounts of bioactive molecules, while seed oils can be considered as alternative vegetable oils for human consumption.